The Steinfeld Cloister Glazing - King, David J. (Gesta, 1998)
The cloister of the Premonstratensian abbey of Steinfeld in the Eifel region in Germany was built in 1499-1517. Its twenty-seven windows were glazed with an extensive typological series, donor figures, and saints in two campaigns between ca. 1522 and 1558. On several occasions the glass was removed, carried away for protection against war damage, and then replaced. Finally, in 1802, through the efforts of John Christopher Hampp of Norwich, it was brought to England where it was sold and dispersed. Thirty-eight panels were acquired by Lord Brownlow and installed at Ashridge Park in the first half of the nineteenth century. These were later given to the Victoria and Albert Museum, London. Two other panels were identified in Bristol. All of this glass was extensively discussed in 1955 in a German publication which included a manuscript description of all the windows from 1719. This led to the identification of nearly ninety panels of Steinfeld glass in many locations, including collections in the U. S. A.; one panel sold at Sotheby's, London, was returned to Steinfeld. These newly identified panels have enabled the correction and refinement of earlier conclusions concerning the iconography and composition, although much further work remains to be done. An appendix lists all extant panels discovered to date.
Keywords: steinfeld

Kloster Steinfeld - Meisterjahn, Bernward (Peda-Kunstführer, 1995)
Keywords: steinfeld

"Wo die Nonnen plieben, welche von Steinfeld ausgewichen sein." Auf den Spuren der Frauen vor dem Hintergrund der religiösen Bewegung des 12. Jahrhunderts - Hirschmann, Frank G. (Jahrbuch für westdeutsche Landesgeschichte, 1994)
Keywords: steinfeld

Prämonstratenser in der Eifel – Steinfeld - Joester, Ingrid (Eiflia Sacra. Studien zu einer Klosterlandschaft, 1994)
Keywords: steinfeld

Die Höfe der Abtei Steinfeld zu Marmagen - Konrads, Manfred (Eifel Jahrbuch, 1994)
Keywords: marmagen; steinfeld

Kloster Steinfeld und seine ostfriesischen Töchterklöster. Anmerkungen zu den Anfängen der Prämonstratenser in Friesland - Löhnertz, Werner (Jahrbuch der Gesellschaft für bildende Kunst und vaterländische Altertümer zu Emden, 1994)
Keywords: steinfeld

Die religiöse und kulturelle Bedeutung der Abtei Steinfeld in der Eifel - Joester, Ingrid (Geschichte im Bistum Aachen, 1992)
Keywords: steinfeld

Steinfeld und die Gründung von Strahov (1142/43). Wann wurde Steinfeld prämonstratensisch? - Löhnertz, Werner (Analecta Praemonstratensia, 1992)
Keywords: steinfeld; strahov